Bacteria in chicken rolls sold by fast food restaurant and their public health significance (Bangladesh Veterinarian, 2016)
This study determined bacterial quality of chicken rolls sold in a fast food restaurant at Bangladesh Agricultural University (BAU) campus. Fifteen chicken rolls (ten premicrowaved and five post-microwaved) were collected. Samples were inoculated into selective media, Eosin Methylene Blue (EMB) agar, Salmonella Shigella (SS) agar, Thiosulphate Citrate Bile Salts Sucrose (TCBS) agar and Mannitol Salt (MS) agar. The total viable count (TVC) and total Staphylococcal count (TSC) of pre-microwaved samples were 4.4 log CFU/g and 4.2 log CFU/g, respectively. In post-microwaved samples, the TVC and TSC were 2.7 log CFU/g and 2.6 log CFU/g, respectively. Microwave treatment significantly reduced the TVC and TSC in the chicken rolls (P